Knowledge, attitudes and practices on the management of dentoalveolar trauma in caregivers of children and adolescents - Colmenares-Vargas, Kimberlin Verónica del Carmen; Morales-Achury, Claudia Jazmín; Otálora-Sarmiento, Gina Estefanía; Angarita-Díaz, María del Pilar; Angarita-Díaz, Karen Mercedes; Quintana del Solar, Carmen Inocencia (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Introduction: Adequate immediate management of dentoalveolar trauma (DT) can improve the prognosis of fractured or avulsed teeth. The aim was to assess knowledge, attitudes, and practices (KAPs) on DT management in parents or caregivers of children and adolescents aged 3 to 15 years in Villavicencio, Colombia. Methods: Descriptive study with a representative sample of 383 parents or caregivers from different boroughs. An instrument previously validated in Peru was used. It was adapted to Colombian terminology with a focus group (Aiken's V: 0.92) and then pilot tested, obtaining a Cronbach's alpha of 0.768. Following validation, it was applied to the entire sample. Statistical analysis was carried out using the U-Mann-Whitney and Kruskal-Wallis tests. Results: A lack of information on dental first aid was identified in 80.7 % (n= 309). Only 38.1 % (n= 146) knew how to transport a tooth or fragment, although 68.1 % (n= 261) would seek dental care in a dental emergency, and 73.4 % (n= 281) would seek immediate care. Most parents, 91.1 % (n= 349), would not attempt re-implantation in the event of tooth avulsion, and 62.9 % (n= 241) would not search for the fragment in the event of tooth fracture. Conclusion: KAPs for managing DT in children and adolescents are lacking among most parents and caregivers. There is a significant relationship between the three dimensions and three factors: previous experience, having received information, and educational level.